Physical Activity and Onset of Acute Ischemic Stroke: The Stroke Onset Study - Mostofsky, Elizabeth (Oxford University Press, 2011)
Regular physical activity is known to decrease the risk of cardiovascular disease, but the risk of ischemic stroke immediately following moderate or vigorous physical activity remains unclear. The authors evaluated the risk of acute ischemic stroke immediately following physical activity and examined whether the risk was modified by regular physical activity. In a multicenter case-crossover study, the authors interviewed 390 ischemic stroke patients (209 men, 181 women) at 3 North American hospitals between January 2001 and November 2006. Physical activity during the hour before stroke symptoms arose was compared with usual frequency of physical activity over the prior year. Of the 390 subjects, 21 (5%) reported having engaged in moderate or vigorous physical activity during the hour before ischemic stroke onset, and 6 subjects had lifted an object weighing at least 50 pounds (≥23 kg) during that hour. The rate ratio for ischemic stroke was 2.3 (95% confidence interval (CI): 1.5, 3.7; P < 0.001) for moderate or vigorous physical activity in the previous hour and 2.6 (95% CI: 1.1, 5.9; P = 0.02) for lifting 50 pounds or more. People who reported engaging in moderate or vigorous physical activity at least 3 times per week experienced a 2-fold increased risk (95% CI: 1.2, 3.3) with each bout of physical activity, as compared with a 6.8-fold risk (95% CI: 2.5, 18.8) among more sedentary subjects (P for homogeneity = 0.03).